(untitled) (Journal of Shaheed Suhrawardy Medical College, 2021)
Anatomic consideration: Flexor pollicis longus (FPL) tendon arises from volar aspect of middle third of radial shaft and from the lateral aspect of interosseous membrane. The anterior interosseous branch of median nerve innervates the muscle in the proximal/mid forearm. Blood supply is predominantly from radial artery. Abstract Purpose: The purpose of this study was to evaluate the results of repair and one stage reconstruction of FPL injury and to find out complications and rupture rate and effectiveness of repair and reconstruction. Method: This retrospective review was carried out in Bangabandhu Sheikh Mujib Medical University from January 2015 to December 2018. 30 consecutive patients were enrolled in the study. 4 strands core suture with simple circumferential suture were used for repair and reconstruction. Tendon transfer was done in few cases. Power grip, active and passive range of motion, American Society for Surgery of the Hand criteria and Buck-Gramcko criteria were used for outcome assessment. Results: Out of 30 patients, 20 (67%) were male and 10 (33%) were female. Mean age was 30 years. Mean follow up period was 1.5 years. All cases were due to various type of cut injuries. In subjective assessment 40% patients achieved excellent, 50% good, 10% fair results. Our rupture rate was 0%. Mean power grip, pinch grip strength of index and key pinch strength were 87.5%, 68.18% and 86.66% respectively from contralateral normal hand. Active range of motion of IP joint was 64.28% of normal side. Conclusions: Use of 4 strands core sutures and early active motion give good to excellent results in 90% cases of repair, reconstruction and tendon transfer in FPL injuries with 0% rupture rate J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 20-26